Re-tooling apparatus of liberalisation with social concerns in shifting paradigm of globalised Indian economy - Rastogi, T.N. (1996)
With the background of India of Gandhi-Nehru dreams, the author discusses the critical areas of our economy which the liberalisation policy, on its four pillars, is targeting. He then presents a brief comparison of India's performance with some nations undergoing the reform process. Reassured with intentions of the present Central government, he concludes, stressing the need for laying emphasis on our social concerns in the reform agenda. - Reproduced
Keywords: Liberalization - India; Economic liberalization